Análise e avaliação de desempenho dos sistemas móveis celulares em Pau dos Ferros-RN - Barros, Igor Moisés Costa (Universidade Federal Rural do Semi-Árido, 2018)
Cellular mobile telephony, since its inception, is constantly evolving and expanding. However, even today, operators have not been able to serve an entire population of standard quality, especially in small regions. Based on this, the present work aimed to measure the quality of mobile cellular telephony (Tim and Vivo) in the city of Pau dos Ferros-RN, through measurements of download, upload, latency and power received, performed in several city districts, using the application for Android platform, OpenSginal. After the measurements, it will be possible to know which locations have the best case rate data transmission, response time for these transmissions and the power received, as well as the location for the worst case.
Keywords: Telefonia; Telephony; Rede móvel; Mobile network; Internet; Internet; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA